Management of Digital Media Use in Integrating Local Wisdom in Elementary Schools - Asti Susanti; Ade Tutty Rokhayati Rosa (Papanda Publisher, 2026)
The rapid integration of digital media in elementary education presents a paradox: while enhancing pedagogical delivery, it risks eroding local wisdom without systematic cultural intentionality. This study examines digital media management for local wisdom integration through the Plan-Do-Check-Act (PDCA) framework. Employing qualitative descriptive design, this research investigated practices at two purposively selected elementary schools in West Java, Indonesia. Data were collected through classroom observations (24 sessions), semi-structured interviews with principals and teachers (n=8), student interviews (n=12), and document analysis, then analyzed using Miles-Huberman procedures with source triangulation for trustworthiness. Findings reveal that while both schools successfully implement digital media with high student engagement (88%), local wisdom integration remains severely limited (8% of observed lessons). Analysis across PDCA phases demonstrates systematic gaps: planning lacks cultural grounding, implementation prioritizes generic content, evaluation focuses exclusively on academic outcomes while neglecting cultural dimensions, and follow-up emphasizes technical rather than culturally-responsive pedagogical development. Teachers demonstrate reasonable technical proficiency but lack conceptual frameworks for bridging technology and culture. Results indicate incomplete PDCA implementation characterized by